Green tea as a promising extract of active food packaging - Vilarinho, Fernanda (2017)
Introduction: Tea is one of the most popular and frequently consumed beverages in the world and its consumption dates back to more than 2000 years in China and then spread to other areas including Japan and later on to Europe (Zhao et al., 2014). Green tea is produced from Camellia sinensis (L.) Kuntze leaf infusion and is well known for its pleasant flavour and is associated with positive health effects. The biological activity of green tea is related with the considerable amount of catechins and other phenolic compounds, in particular flavonols and phenolic acids, present in its composition (Zhao et al., 2014). These phenolic compounds prevent the oxidative damage through their antioxidant activity and also reduce the risk of cancer, cardiovascular and neurodegenerative diseases (Lorenzo et al., 2014). The process of oxidation is one of the most common mechanisms of degradation of foodstuffs and it can alter food texture and colour, decrease nutritional quality, develop off-odours and also produce possible toxic compounds. As a consequence, the shelf-life and commercial acceptability of the food products decrease. Currently, one of the major concerns of the consumers is the impact of food on health. In line with this, food industry is trying to substitute synthetic additives by natural compounds. These can be directly added to food or incorporated in food packaging with the aim of being controlled released throughout the product shelf life. This concept is so-called Active packaging and allows the packaging to positively interact with foods to increase food shelf-life. This interaction can be due to the intended release of compounds from packaging to the foods or to their headspace, or due to the scavenging of compounds by the packaging from the packaged foods. Due to the antioxidant capacity of green tea, its extract can be proposed as an alternative to synthetic antioxidants (Giménez et al., 2013). In fact, it has already been applied in active food packaging. Material and Methods: The present review focuses on the application of green tea extract in active packaging. In this regard, an extensive bibliographic research was carried out in order to evaluate the polymers already used to incorporate green tea extract, as well as the mechanical and barrier properties and efficiency of these packaging systems in contact with foods. Results and Discussion: The chemical composition of tea leaves on active compounds with antioxidant activity is well documented. Bioactive constituents of the tea leaves include catechin gallates such as epigallocatechin gallate and gallocatechin gallate (López de Dicastillo et al., 2011). However the levels of these compounds depend on many factors, such as the edaphoclimatic conditions and drying conditions of the Camellia sinensis leaves. Moreover the extraction and analysis methods can also have a great influence in their content. Green tea extract has already been incorporated into different polymers. In fact, most of them are edible such as proteic films from distilled dry beans (Yang et al., 2016), agar (Lacey et al., 2014), chitosan (Siripatrawan et al., 2012; Siripatrawan et al., 2010) and gelatine (Hong et al (2009). Green tea extract (GTE) can offers protection against oxidation, significantly reducing rancidity and thereby extending the shelf-life of packaged foods. Moreover the sensory analysis also demonstrated that packaged food was unaffected by GTE (Carrizo et al., 2016). According to Yang et al. (2016), the incorporation of the GTE did not alter the physical properties of the films. According to Siripatrawan et al. (2010), the incorporation of GTE improved the mechanical and water vapour barrier properties. In general, GTE provides a very positive impact in the reduction of oxidation of all types of food, from aqueous to fatty (López de Dicastillo et al., 2011), although most of the studies selected meat (e.g. pork, pork sausages, pork loins), or fish products (e.g. fillets of hake, salted sardines) to test the efficiency of the active films. Conclusion: Green tea has great potential of application in active food packaging due to its antioxidant capacity. Therefore, in the near future, is it possible that new food packaging based on GTE will arise in the market. However, more studies are require to elucidate about the concentrations of GTE that do not affect or affect positively the mechanical or barrier properties of the packaging and that are effective as oxidation inhibitors of packaged foods